Experimental Investigations on Drilling of Cortical Bone - Singh, Gurmeet (My University, 2019)
The implication of machining for bone is widely accepted during the different orthopedic, dental and neuro surgeries. There are some mechanical and thermal damages observed, while machining bone for some specific reasons.This secondary damage to the bone cells and tissues may cause failure to the bone joint. Heat generation around the drill site may lead to osteonecrosis and further the body part may get collapse. Novel techniques are regularly encouraging in orthopedic, dental and neuro surgeries to minimize the thermal and mechanical invasive and improve the quality and efficiency. Ultrasonic assisted drilling method is one from these techniques, in which ultrasonic vibrations are superimposed on rotating tool.The main concern with bone drilling process is to reduce the damages to the bone tissues around the drill site by means of some technological improvements. In this study, experimental examinations have been done to understand the behavior of bone to thermal and mechanical damage around the drill site with respect to the different drilling parameters and experimental conditions. The experiments included the measuring of heat generation around the drill site, thrust forces during drilling process, diametric delamination of drilled holes and pullout study of bone-screw joint. In order to justify the ultrasonic assisted bone drilling (UABD), a comparison of ultrasonic assisted bone drilling (UABD) process with conventional bone drilling (CBD) process for above said outcomes has been done. The conduct of drilling parameters i.e rotational speed (rpm), Feed rate (mm/min), drill point angle (degree), drill helix angle (degree) was evaluated and analyzed on various levels using Taguchi optimization. From the optimization, most favorable condition of drilling parameters has been found to control the different bone drilling outcomes studied in this thesis. Further, ANOVA analysis was used to check the percentage contribution of each involved parameter on the output which was optimized individually. The effectiveness of the selected parameters with their levels has also evaluated by calculating P-value in ANOVA table. The parameters considered to be significant when P≤0.05 for Rotational speed, Feed rate and drill specifications (Point angle and helix angle). Thereafter, microscopic characterization techniques i.e Histopathology and Scanning Electron Microscope (SEM) were employed to understand the thermal and mechanical damage with respect to the exposed temperature and thrust forces to the bone during experiments. Damaged osteocytes were observed in histopathology study and confirmed that increasing heat generation and thermal damage around the drill siteis directly interpersonal.SEM was used to detect the surface topography in view of surface damage and microcracks generated during the drilling related to the mechanical damage. Finite element analysis (FEA) is conducted and model is developed using DEFORM 3D software to compare the results for ultrasonic assisted bone drilling (UABD) and conventional bone drilling (CBD) process. The main focus of the study is on the mechanistic behavior of different bone drilling parameters under the influence of ultrasonic assisted tooling conditions and influence of individual parameters on desired responses help to draw the final conclusions and recommendations for its applications in orthopedic surgeries
Ph.D Thesis
Keywords: Bone drilling; Ultrasonic Assisted Drilling(UAD); Heat Generation; Thrust forces; Pullout; Osteonecrosis; Histopathology; Scanning Electron Microscopy(SEM); Finite Element Analysis(FEA)